Accuracy of models for mechanical properties of concrete subjected to the elevated temperature - A. Mohammed, Azad; ., . (International Journal of Engineering and Technology, 2018)
For the fire safety design of concrete structures and repairing damaged members as a result of fire exposure, accurate equations for the residual mechanical properties of concrete usually required. Equations given by the international codes or proposed by the researchers may not be accurate and should be assessed carefully when applied on the locally produced concretes. In this research study, available data on the residual compressive strength, elastic modulus and tensile strength of concrete mostly from Iraqi sources were collected, analyzed, and equations were proposed for calculating the three mechanical properties. Different response of past proposed models for the mechanical properties against the collected test data is observed. Using regression analysis equations were proposed for calculating the residual compressive strength, splitting tensile strength and elastic modulus of heated concrete. Simple statistical tests indicate that the proposed equations are accurate and safe. There is a chance to use some equations proposed by the researchers and codes but the equation given by the ENV 1992 Code for the residual elastic modulus was found not accurate.Â Â